أنماط الراوي في "الملهاة الفلسطينية" لإبراهيم نصر الله - البياتي، سوسن هادي جعفر; شهاب، داليا حميد Shehab, Dalia Hamid (جامعة تكريت - كلية التربية للعلوم الإنسانية, 2016)
الحمد لله الذي بعث رسوله بالحق، والصلاة والسلام على النبي الأمي الذي هدانا بما عمل وبما به نطق، وعلى آله وصحبه أفضل صلاة، وأتم سلام إلى يوم الحساب، ولا يسعنا في هذه الخلاصة إلا أن نسلط الضوء على بعض السمات التي تنبه لها البحث والتي تعد خلاصة للموضوع، فقد رأينا في هذا البحث، أن الراوي هو أحد أركان العمل الروائي، فوراء الظواهر الفنية من أفعال وشخوص، ومكان وزمان، يقف راو، يتولى مهمة الترتيب والتنضيد داخل النص الروائي، ولهذا تعددت الدراسات والمقاربات النقدية لدراسته بوصفه ركنا يحدد أسلوب العمل الروائي. أما الملهاة الفلسطينية لإبراهيم نصر الله فهو مشروع روائي يضم سبع روايات (طيور الحذر، طفل الممحاة، زيتون الشوارع، أعراس آمنة، تحت شمس الضحى، زمن الخيول البيضاء، قناديل ملك الجليل)، وكل رواية مستقلة تماما عن الأخرى. وقد اقتضت طبيعة العمل في البحث أن نقسمه على ثلاثة أنماط: النمط الأول: الراوي العليم (كلي العلم) فهو الذي يمتلك قدرة غير محددة للوقوف على الأبعاد الداخلية والخارجية للأشخاص فيكشف عن العوالم السرية للأبطال، ويستخدم ضمير الشخص الثالث (هو / هي)، ذلك أن رواية الشخص الثالث تركز في أبسط أنماطها على البطل، فنحن لا نرى أبدا ما يستطيع رؤيته فهو دائم الحضور في كل مكان وزمان. وهذا النمط تتسم به الروايات الكلاسيكية غالبا. النمط الثاني: الراوي محدود العلم ويختلف هذا النمط عن النمط الأول فيستخدم ضمير الشخص الأول (أنا/ نحن) بطريقة اعترافيه، وضمير الشخص الثاني (أنت /وأنتم)، فالضمير المتكلم / أنا له القدرة على إزالة الفروق الزمانية والسردية بين السارد والشخصية. وهو سمة الروايات المعاصرة. النمط الثالث: الرواة المتعددون (الأصوات السردية) كثيرا ما يحاول الكاتب الاستعانة بأكثر من راو في النص الواحد حسبما تفتضيه طبيعة السارد والمسرود. وأخيرا، فإني آمل أن يكون هذا البحث قد حقق أهدافه المنشودة، فإن وفقنا فهذا فضل من الله، وإن أخفقنا فحسبنا أنا حاولنا والله الموفق.
Praise be to God, who sent a messenger to the right, and peace and blessings be upon the Prophet illiterate who has guided us, including business, including its pronunciation, and his family and companions better pray, and did peace to the day of reckoning, we can not at this conclusion, but to highlight some of the features that stimulate her research, which is Summary of the subject, we have seen in this research, that the narrator is one of the pillars of work novelist, Behind the phenomena of technical actions and characters, and the place and time, stands Rao, the task of arranging and typesetting within the text novelist, and that there were many studies and approaches cash to study it as a cornerstone determines the method of work novelist . The Palestinian comedy Ibrahim Nasrallah is novelist project includes seven novels (caution birds, baby Eraser, Olive streets, Wedding secure, under the forenoon sun, the time of white horses, jellyfish king of Galilee), each novel is completely independent of the other The nature of the work arises in the search to : divide it into three patterns The first pattern: Narrator Aleem (omniscient) is the one who has the ability of non-specific to determine the dimensions of the internal and all worlds secret of Champions, and uses the external people conscience of the third person (he / she), so that the novel third- person focus in the simplest patterns of the hero, we never see what you can see is a permanent presence in every place and time. Type II: Narrator limited science and differs from the pattern of the first type uses the conscience of the first person (I / we) in a manner and the conscience of the second person (you / and you), conscience speaker / I has the ability to remove differences temporal and narrative between narrator and character Type III: multi-narrators (narrative votes) often try to use more than one writer per Rao in the text as required by the nature of the narrator and listed Finally, I hope that this research has achieved its objectives, and guide us for that, as well as from God, and that we have failed is calculated The last prayer is that all praise be to Allah, Lord of the Worlds And prayers and peace be upon the Messengers and God and all the Sabha
Keywords: السرد الأدبي -- الرواية العربية -- الشخصيات التراثية -- النقد الأدبي -- نصر الله، إبراهيم